Watching Moonlight in the Twilight of Obama. (August 2017) - Kannan, Menaka; Hall, Rhys; Hughey, Matthew W.
Now months into the already turbulent presidency of Donald Trump, and in the wake of both the Obama presidency and Moonlight 's awkward ceremonial win for "Best Picture" at the 2017 Academy Awards, what are the meanings of Moonlight ? We contend that the film's polysemy both reproduces and challenges the continuing fight for lesbian, gay, bisexual, transgender, and queer; racial; class; and gender equality and representational struggles of marginalized peoples on the silver screen. With complexity, the film trades in and tests racial stereotypes and understandings of black families; relishes in the heterogeneity of black and Latinx identities; displays cultural contradictions at the heart of racism, heteronormativity, and hegemonic masculinity; and refuses to shy away from topics of love, lust, and loss. Together, the film is an epic—a sweeping homage to social transformation and to the nobility and negativity of the human condition.